Is Planting Equitable? An Examination of the Spatial Distribution of Nonprofit Urban Tree-Planting Programs by Canopy Cover, Income, Race, and Ethnicity. (May 2017) - Watkins, Shannon Lea; Mincey, Sarah K.; Vogt, Jess; Sweeney, Sean P.
This article examines the spatial distribution of tree-planting projects undertaken by four urban greening nonprofit organizations in the Midwest and Eastern United States. We use a unique data set of tree-planting locations, land use data, and socioeconomic information to predict whether a census block group ( n = 3, 771) was the location of a tree-planting project between 2009 and 2011. Regression results show tree-planting projects were significantly less likely to have occurred in block groups with higher tree canopy cover, higher median income, or greater percentages of African American or Hispanic residents, controlling for physical and socioeconomic conditions. In addition, when canopy cover or income was low, plantings were even less likely to have occurred in neighborhoods with high percentages of racial or ethnic minorities. Findings suggest nonprofit plantings might reduce existing income-based inequity in canopy cover, but risk creating or exacerbating race-based inequity and risk leaving low canopy minority neighborhoods with relatively few program benefits.